Tantangan UMKM Batik Lek 'Iwon di Era Milenial - Pratama, Andika; Artika , Windi; Hakim , Ari Maulana; Esperansa Ki , Maria; Sahrin, Randi Alfi; Arnoldus G T , Mateus; Wulandari , Juwinda; Prawita, Dika (Inspirasi: Jurnal Pengabdian Masyarakat, 2024)
This observation was successfully carried out at Taman KT 1/433 RT 36/RW 09, Petehan Village, Kraton, Yogyakarta on October 14 2024, by students from the Management Study Program, Faculty of Economics, UST, with the aim of introducing and applying the teachings of Ki Hajar Dwantara's leadership trilogy to the community. local. The community service activities carried out by students from the UST Faculty of Economics Management Study Program were successfully carried out smoothly and were warmly welcomed by the owner of the batik business named Lek Iwon. This activity was carried out with the aim of finding out the obstacles faced by Lek Iwon Batik MSMEs and providing solutions.The method used is to conduct interviews directly at the batik maker's place. Based on the results of these observations, the results of the observations are WithTri N (Niteni, Nirokke, Nambahi). This principle teaches a learning approach based on observation (Niteni), good imitation (Nirokke), and observation (Nambahi). This can imitate good financial practices, and always innovate to increase financial efficiency and productivity.